Bosnia and Herzegovina : Technical Assistance Report-Report on Government Finance Statistics Technical Assistance Mission, (October 1-5, 2018). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Technical Assistance Report discusses details of the mission conducted to support the Bosnia and Herzegovina authorities, with a specific focus on the Republic of Srpska (RS), in improving government finance statistics (GFS) for decision making. The mission rounded off research to establish appropriate reconciliation procedures, although some statistical discrepancies remain. The goal is to use the compilation and reconciliation procedures for quarterly and annual GFS reporting to Eurostat and the IMF's Statistics Department. The May 2018 mission initiated the development of a standardized compilation procedure for nonbudgetary public sector units, and more specifically extrabudgetary units. The report recommends focussing on investigating possibilities into incorporating these compilation files into the wider GFS and macroeconomic statistics compilation. On analysis of the financial statements, the mission assessed that Accrued revenues and received donations also require and adjustment to following the European System of National and Regional Accounts 2010 and Government Finance Statistics Manua 2014 recording.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet